1995
DOI: 10.1007/bf03349833
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid blood flow evaluation by color-flow doppler sonography distinguishes Graves’ disease from Hashimoto’s thyroiditis

Abstract: Thyroid hypoechogenicity at ultrasound is a characteristic of autoimmune thyroid diseases, with an overlap of this echographic pattern in patients affected by Graves' disease or Hashimoto's thyroiditis. Aim of the present paper was to study the thyroid blood flow (TBF) by color-flow doppler (CFD) and peak systolic velocity (PSV) at the inferior thyroid artery in 37 Graves' and 45 goitrous Hashimoto's thyroiditis patients. CFD pattern was defined as normal (or type 0): TBF limited to peripheral thyroid arteries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
3
5

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(118 citation statements)
references
References 12 publications
6
104
3
5
Order By: Relevance
“…The inclusion criteria were: (1) positivity for anti-thyroglobulin and/or anti-peroxidase antibodies (TgAb and TPOAb respectively) at high titres; (2) negativity for anti-TSH receptor antibodies (TRAb); (3) thyroid ultrasound imaging suggestive of a chronic thyroiditis (20); (4) no clinical history of hyperthyroidism; (5) no treatment with drugs known to induce thyroid autoimmunity and/or dysfunction (cytokines, lithium, amiodarone); (6) no pregnancy in the last 12 months prior to enrolment; and (7) non-smoker during the month prior to enrolment. The control group comprised 20 healthy subjects recruited from this establishment, matched for sex and age with the HT patients.…”
Section: Subjectsmentioning
confidence: 99%
“…The inclusion criteria were: (1) positivity for anti-thyroglobulin and/or anti-peroxidase antibodies (TgAb and TPOAb respectively) at high titres; (2) negativity for anti-TSH receptor antibodies (TRAb); (3) thyroid ultrasound imaging suggestive of a chronic thyroiditis (20); (4) no clinical history of hyperthyroidism; (5) no treatment with drugs known to induce thyroid autoimmunity and/or dysfunction (cytokines, lithium, amiodarone); (6) no pregnancy in the last 12 months prior to enrolment; and (7) non-smoker during the month prior to enrolment. The control group comprised 20 healthy subjects recruited from this establishment, matched for sex and age with the HT patients.…”
Section: Subjectsmentioning
confidence: 99%
“…The availability of color flow doppler sonography (CFDS), a rapid, informative, and non-invasive technique, has recently allowed direct measurement of intrathyroidal blood flow (10)(11)(12)(13)(14)(15)(16)(17). Using CFDS it has been shown that intrathyroidal blood flow, which can be quantitated by measurement of peak systolic velocity (PSV), is greatly increased in patients with untreated Graves' hyperthyroidism (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Several qualitatively classifications of intrathyroidal vascular patterns distinctive to specific pathological entities have been proposed, with that of Vitti's being the most widely used in clinical practice (9). This classification describes easily and quickly the intraparenchymal of thyroid autoimmunity, and to compare its sensitivity and specificity with other gray-scale sonographic findings.…”
mentioning
confidence: 99%